YIELD POTENTIAL AND VARIABILITY OF TWO MAIZE COMPOSITES - MIRANDA FILHO, JOSE BRANCO DE; GORGULHO, ELIANA PATRÍCIA (International Journal of Maize & Sorghum, 2010)
In the 1994/95 season, 1272 accesses of the Active Maize Germplasm Bank (CENARGEN-EMBRAPA) were evaluated in several locations previously chosen to assure incidence of leaf diseases caused by Phaeosphaeria maydis and Exserohilum turcicum. Two composite populations named RPM (Resistant to P. maydis) and RET (Resistant to E. turcicum) were synthesized after recombination of 46 and 34 accesses, respectively. After two generations of recombination, a sample of 300 open pollinated ears (half-sib families) was chosen from each population. Families were evaluated in Anhembi (SP) in the 1999/00 season in six experiments with 50 families representing each population. The hybrid Master (Novartis Seeds) was used as check. The additive genetic variance (σ2A) and the coefficient of heritability (h2F) were estimated for ear yield, plant height and ear height. Mean yield of the RPM composite was 5.707t/ha (77% of the hybrid check). Plant and ear height means were 19.4% and 36.3% higher than check. Parameters of variability were high with estimates of σ2A and h2F of 554.73 (g/pl)2 and 0.58, respectively. Mean yield of the RET composite was 4.393t/ha (56.7% of the hybrid check). For plant and ear height, means were slightly lower than check. In the RET composite the variability for yield was less expressive with estimates of 195.58 (g/pl)2 and 0.40 respectively.